Effects of bovine urinary nitrogen on the nitrogen cycle of a shortgrass prairie - Stillwell, Mark A., author; Woodmansee, Robert G., advisor; Rittenhouse, Larry R., committee member; Parton, William J., committee member; Porter, Lynn K., committee member (Colorado State University. Libraries, 1983)
Free grazing ungulates were hypothesized to exert a significant influence on the nitrogen cycle of a grazed shortgrass prairie ecosystem. Two field studies were performed from May 1980 through March 1982 in shortgrass prairie pastures at the Central Plains Experimental Range northeast of Fort Collins, Colorado. The objective of the first study was to quantify seasonal variation in nitrogen ingested by free grazing heifers and the partitioning of the ingested nitrogen among urine, feces, and storage in animal bodies. A herd of eight yearling heifers in a 125 ha. pasture consumed 116 kg of forage nitrogen during the growing season and 91 kg of forage nitrogen during the dormant season. This was only 10% of peak standing crop of forage nitrogen. Ten percent of the nitrogen ingested during the study period was incorporated into body growth. Excreted nitrogen was partitioned between urine and feces at 54% and 46% for the growing season and 45% and 55% for the dormant season. This was a deposition rate of 1.6 kg N/ ha. for the pasture. The objective of the second field study was to determine the fate of urinary nitrogen once it was returned to various soils in a pasture. Simulated urine with l5N labeled urea was added at the rate of 45 g/m² to the soil at three sites on a catena. Urea hydrolysis was rapid at all sites with little urea remaining after four days. Over a 15 month period a sandy ridgetop and a clay swale soil retained about 70% of the added nitrogen. Only 40% was recovered from a midslope soil. Elevated calcium levels in the ridgetop and high clay content in the swale soil were important in the conservation of nitrogen. Cattle grazing was shown to be important in the N cycle by processing 10% of the standing N and depositing it in concentrated spots on the soil. Long term effects indicate that up to 50% of a community may be affected at any time.
Keywords: Grassland ecology; Nitrogen cycle; Nitrogen excretion; Cattle